2015
DOI: 10.1002/2015jc010970
|View full text |Cite
|
Sign up to set email alerts
|

Minimal model for double diffusion and its application to Kivu, Nyos, and Powell Lake

Abstract: Double diffusion originates from the markedly different molecular diffusion rates of heat and salt in water, producing staircase structures under favorable conditions. The phenomenon essentially consists of two processes: molecular diffusion across sharp interfaces and convective transport in the gravitationally unstable layers. In this paper, we propose a model that is based on the one‐dimensional description of these two processes only, and—by self‐organization—is able to reproduce both the large‐scale dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…where = ∕ , = − ∕ are defined in LAKE model according to the equation of state from McCutcheon et al (1993). Stratification is stable when R > 1, but in the interval 1 < R < 10 the diffusive regime of double-diffusive convection is anticipated (Kelley et al 2003, Toffolon et al 2015. Double diffusion leads to effective vertical mixing, potent to hinder the TeM development.…”
Section: Temperature Maximum 331 Salinity-related Effectsmentioning
confidence: 99%
“…where = ∕ , = − ∕ are defined in LAKE model according to the equation of state from McCutcheon et al (1993). Stratification is stable when R > 1, but in the interval 1 < R < 10 the diffusive regime of double-diffusive convection is anticipated (Kelley et al 2003, Toffolon et al 2015. Double diffusion leads to effective vertical mixing, potent to hinder the TeM development.…”
Section: Temperature Maximum 331 Salinity-related Effectsmentioning
confidence: 99%
“…However, Stern numbers have been reported as varying from O(10 −3 ) to O(10 2 ) for finger systems. Recently, Traxler et al (2011) reported Stern numbers St = 9.4 and St = 76 for DNS simulations with density ratios R ρ = 2.0 and R ρ = 1.2. These density ratios are comparable to Case 3 and Case 4, allowing us to compare our results with these DNS simulations.…”
Section: Casementioning
confidence: 99%
“…Based on a 3-D DNS model, Traxler et al (2011) found Stern numbers St = 9.4 and St = 76 for R ρ = 2.0 and R ρ = 1.2, respectively. Our simulations for R ρ = 2.04 (Case 3) and R ρ = 1.19 (Case 4) yield lower average Stern numbers of approximately 0.73 and 1.95, respectively (Fig.…”
Section: Cases 3 and 4: Salt Fingersmentioning
confidence: 99%